Efficacy of Toothpaste in Reducing Micro-Flora Isolated from Toothbrush - Gautam, Bikram; Pokhrel, Sabi; Aryal, Sagar; Basnet, Anup (Kathmandu University Journal of Science, Engineering and Technology, 2018)
Oral cavity is the easiest site of entry of microorganisms during breathing, eating, drinking and brushing which can lead to several bacterial infections in oral cavity, pharynx, larynx, gastrointestinal tracts etc. Toothbrushes commonly used to maintain oral health and prevent dental disease; but unfortunately, how keeping the toothbrush is neglected. A wide range of chemicals have been added to toothpastes in order to produce a direct inhibitory effect on plaque formation and kill microorganisms. The aims of the study were to investigate the relationship between toothbrush keeping place, its microbial content determine the type of micro-flora present in toothbrush kept in different locations and to determine efficacy of toothpaste in reducing micro-flora isolated from toothbrush. Used toothbrushes were taken from 21 individuals. 2 (1 herbal and 1 regular) toothpastes were selected for the study and were collected from local market. Standard pour plate method and plate count method were performed to determine the reduction of microbial load. Out of 21 toothbrushes, 19 (90.48%) were found to be growth positive and 2 (9.52%) were growth negative. Common Gram positive organisms isolates includes Lactobacillus species (20%), Bacillus subtilis (5%), Bacillus megaterium (5%), Stahpylococcus aureus (25%), Staphylococcus epidermidis (10%), Micrococcus species (10%) and Gram negative organisms isolated include Citrobacter freundii (5%), Pseudomonas aeruginosa (5%), Proteus mirabilis (5%), Enterobacter species (5%) and Klebsiella pneumonia (5%). Toothbrushes kept in the toilet/bathroom showed contamination with pathogens. Toothpaste T1 was found to be better at reducing microbial load compared to T2. Toilet/bathroom is the worst place for keeping toothbrushes. Toothpastes have their own patent, specialty and were found to be effective against the microorganisms. Synergistic interactions between the principal components of toothpaste can be considered to be a vital part of their efficacy. Kathmandu University Journal of Science, Engineering and Technology Vol. 13, No. 2, 2017, page: 71-78